Management of lateral lip element in rotation advancement technique for cleft lip repair: Tips and tricks - Gaurav S Deshpande; Alex Campbell (Wolters Kluwer Medknow Publications, 2014)
A new era in cleft lip repair began when Dr. Ralph D Millard introduced his technique of rotation and advancement. In 1987, Mohler described a variation of Millard's unilateral repair that included a columellar extension. In 2005, Fisher introduced the principle of anatomic subunit closure. These techniques can work very well across the spectrum of unilateral clefts of the lip, though challenges arise with wide clefts and those where there is a large discrepancy between the greater lip height and lesser lip height. In cases when the discrepancy is high, the surgeon often tries to gain the necessary lip height on the cleft side by shifting the Noordhoff's point more laterally, sacrificing excessive tissue. This often results in a lateral lip that is hypoplastic, giving an unnatural look to the repaired upper lip. Focus has traditionally been on getting the necessary lip height, sacrificing fullness of the lateral lip element. This paper describes several strategies to optimally manage the lateral lip element in rotation-advancement technique for unilateral cleft lip repair. The results with this technique are encouraging and can be utilized to offset the drawbacks of rotation-advancement technique in very wide and short cleft lips.